Treatment of Crohn's-Related Rectovaginal Fistula With Allogeneic Expanded-Adipose Derived Stem Cells: A Phase I–IIa Clinical Trial. (13th July 2016) - García-Arranz, Mariano; Herreros, Maria Dolores; González-Gómez, Carolina; de la Quintana, Paloma; Guadalajara, Héctor; Georgiev-Hristov, Tihomir; Trébol, Jacobo; Garcia-Olmo, Damián
Abstract : This clinical trial was to determine the safety and feasibility of expanded allogeneic adipose-derived stem cells to treat Crohn's-related rectovaginal fistula (CRRVF). Sixty percent of the nonexcluded patients achieved a complete healing. This is a safe and feasible therapy for treating CRRVF, and the healing success rate appears promising. Abstract: The aim of this clinical trial was to determine the safety and feasibility of expanded allogeneic adipose-derived stem cells to treat Crohn's-related rectovaginal fistula (CRRVF). We designed a phase I–II clinical trial (https://ClinicalTrials.gov, NCT00999115) to treat 10 patients with CRRVF. Patients receiving biological therapy during follow-up were excluded. Curettage was performed, and a vaginal or rectal flap was added if the surgeon considered it necessary. The therapeutic protocol included intralesional injection of 20 million stem cells in the vaginal walls (submucosal area) and fistula tract. Healing was evaluated 12 weeks later. If the fistula had not healed, a second dose of 40 million stem cells was administered. Patient follow-up was 52 weeks from last cell injection. Healing was defined as re-epithelialization of both vaginal and rectal sides and absence of vaginal drainage. Cytokines and immunological blood tests were monitored. Serious adverse events or rejection issues were not observed. Five patients were excluded because biologic drugs were required to treat a Crohn's disease flare-up during follow-up. Cytokine profiles and immunotoxicity assays showed no statistically significant alterations. Sixty percent of the nonexcluded patients achieved a complete healing. Expanded allogeneic adipose-derived stem-cell injection is a safe and feasible therapy for treating CRRVF, and the healing success rate seems promising (60%). The results of this trial encourage further exploration into this therapy. Significance: This may be the first publication in which allogeneic stem cells to treat rectovaginal fistula in Crohn's disease seem to be a feasible and safe treatment. Additional studies are necessary to confirm the efficacy profile of the allogeneic stem cells strategy in a controlled design.